THE MAKING OF NICKNAMES AND PSEUDONYM THROUGH WORD-MAKING TOOLS - Obidova , Azizaxon Davronboy qizi (GOLDEN BRAIN, 2024)
This chapter talks about the semantic properties of the nicknames and nicknames under study, the process of making words and phonetic means. It also highlights word formation models within words; clarifies the structural types of complex nicknames and nicknames as well as, the types generated by abbreviations